IT’S THERE FOR YOU, BUT IS IT #FYP?: A METHODOLOGICAL REFLECTION OF RESEARCHING CONTENT VS. COMMUNITY ON TIKTOK - Messina, Nicole (AoIR Selected Papers of Internet Research, 2021)
With each new online platform comes a new set of methodological challenges when studying its content and the people who reside in that digital space. This paper presents a methodological reflection of studying the exchange of health information and building of community and safe space amongst queer youth on the video sharing and social networking app TikTok. Upon encountering challenges in research related to affordances within the app, further questions are posed about how we go might about studying the nature of content that users, especially those of a specific and historically marginalized group, will come across in their day-to-day engagement with the app, and in so doing exchange information and support with one-another. Existing affordances in the app beg the question of whether content on this platform can truly be studied or understood, even in terms of a simple content analysis, without the direct involvement of users. Replication of the user’s experience, and natural encounter with content of a specific nature, becomes challenging and has its risks.